Gender Inequality in Social Forestry Management of Baduy Farmers in Lebak Regency - Utami, Wahyu Kartiko; Mayrudin, Yeby Ma'asan (Journal of Local Government Issues, 2024)
Baduy are attached to the forest, and the environment depends on forest management. On the other hand, the role and involvement of Baduy women are no less important in forest management to encourage food security for them and their families. This research uses the theory of gender equality; it aims to capture the gender gap in forest management through social forestry programs in the Baduy community to encourage food security. By using a qualitative descriptive method, this research seeks to let reality reveal itself naturally. The study results show that gender inequality still exists in managing social forestry in the Baduy community. This gender inequality can be seen in the minimum absence of access for Baduy women involved in social forestry management. The domestic role of Baduy women dominates in food security efforts through social forestry, but the public role of Baduy women farmers is almost nonexistent. Women's control over social forestry is also limited to the domestic role in the household. In contrast, control in forestry is held by male farmers, with all decisions in the hands of men, making it difficult for women to be present and actively involved. However, this social forestry benefits both male and female farmers, whereas women obtain these benefits indirectly through their husbands, who are actively involved as managers of social forestry.